PENGARUH STRATEGI DIFERENSIASI TERHADAP LOYALITAS PELANGGAN JASA BISNIS TRANSPORTASI (Kasus pada PT. Eka Sari Lorena Perwakilan Pekanbaru) - Triyandi, Dian; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Transportation is a very important tool in helping the economy. An area can not be completely stand alone in meeting the needs of their region, so that the area in need of other areas as support, is a means of connecting transport or transport. Regional development, both in economics, education and culture requires adequate transport services. Without transportation as a means of support can not be expected satisfactory results in business development and improvement of the economy of a region. As a business engaged in transport services that would arise related to the differentiation strategy that will have an impact on customer loyalty. Therefore, this study will examine the effect aimed differentiation strategy consisting of product differentiation, service differentiation, personnel differentiation and image differentiation and its effect on customer loyalty PT. Eka Sari Lorena representative pekanbaru. PT. Eka Sari Lorena is one stu company engaged in the business services provider of ground transportation. In line with the research strategy of differentiation as a variable X and variable Y. customer loyalty as the number of respondents were 100 subscribers. The results of this study based on the results of the t test (a partial test hypotheses about the parameters of the regression coefficients which aims to determine whether the independent variables have a significant effect on the dependent variable). T known (4,850)> t table (1.985) and Sig. (0.000) <0.05. This means that variables significantly influence the differentiation strategy lotalitas customers. From the above analysis it can be concluded that the influence of strategic differentiation and customer loyalty at. PT. Eka Sari Lorena representative Pekanbaru.Keyword : Strategic Differentiation, Customer Loyalty